Proteome Bioinformatics - Hubbard, Simon J.; Jones, Andrew R. (Methods in Molecular Biology™, Methods and Protocols, 2010)
The field of proteomics moves rapidly, as new methods, techniques, applications, standards, models and software appear almost on a daily basis. In Proteome Bioinformatics, expert researchers explore this ever-changing field, providing the reader with a mix of review and methodology chapters which address the fundamentals of analysis methods, algorithms, data standards and databases. Chapters include practical considerations for analyzing database search results, annotating genomes, speeding up searches, and responding to specific data processing challenges. As a volume of the highly successful Methods in Molecular Biology series, this work provides the kind of detailed description and implementation advice that is crucial for getting optimal results. Comprehensive and ground-breaking, Proteome Bioinformatics is an essential guidebook for the novice and expert alike, covering topics that address a wide range of data analysis and management problems